Comparison of The Effect of Subacute Treatment of Mitragyna speciosa korth Standardized Methanol Extraet and Morphine on the Development of Antinociceptive Tolerance to Thermal Noxious Stimuli in Swiss Albino Mice - Laila, Ab Mukmin (2008)
Mitragynine is the main constituent of 25 alkaloids contained in Mitragyna speciosa Korth standardized methanol extract It acts on mu and delta opioid receptor as an agonist, similar to morphine and produce analgesic effect in response to both thermal and mechanical pain stimulus. 1bis research was to study the effect of subacute administration M speciosa Korth on development of tolerance, and comparing it to morphine. Methodology Swiss albino mice were divided into 3 groups, each were subjected to daily doses of either M speciosa Korth, morphine or placebo, given subcutaneously for 6 days. They were subjected to daily hot plate thermal noxious stimuli 30 minutes after administration, until the sign of pain exhibited (hind-paw licking, jumping). On day 7, the M speciosa Korth administered mice were given a single challenge dose of M speciosa Korth while the morphine and placebo treated mice were given morphine and subjected to hot plate test for 120 minutes, at 30 minutes interval. The changes in baseline latencies were also quantified. The antinociceptive response was quantified as percentage of maximal possible effect, %MPE. Results M speciosa Korth standardized methanol extract administered mice showed increase antinociceptive response by day 6 when compared to placebo (p<O.Ol), while morphine treated mice showed minimal tolerance by day 6. The baseline latencies were X significantly increase for both M speciosa Korth and morphine group post treatment when compared to pre treatment (p<O.Ol), however, the difference between groups were not significant (p>0.05). Conclusion There was no development of tolerance, but an increase in analgesic effect in mice administered with M speciosa Korth methanol extract in subacute duration. In comparison, morphine treated mice showed minimal tolerance in antinociceptive response by day 6, although the different between groups was not statistically significant